2019
DOI: 10.1080/16742834.2020.1696650
|View full text |Cite
|
Sign up to set email alerts
|

The global response of temperature to high-latitude vegetation greening in a two-dimensional energy balance model

Abstract: The relationship between vegetation greening and climate change remains unclear due to its complexity, especially in drylands. Against the background of global warming, arid and semi-arid areas, including mid-latitude deserts, are most sensitive to climate change. In recent decades, the mechanisms underlying the relationship between vegetation greening and climate change have been widely discussed in the literature. However, the influence of vegetation greening in high latitudes on regional climate has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Evapotranspiration, however, did not change much at the high latitude, therefore, indicating the limited effect of evaporative cooling on mean temperature at the zone. Additionally, the cooling effect of evapotranspiration may be cancelled out by the dominating effect of albedo changes as studies have shown (Jeong et al, 2011;Pearson et al, 2013;Shen et al, 2015), especially with the recent greening, which has a warming effect through reduced albedo (Forzieri et al, 2017;Bi et al, 2020).…”
Section: Spatial Trend Of Temperature and Precipitationmentioning
confidence: 99%
“…Evapotranspiration, however, did not change much at the high latitude, therefore, indicating the limited effect of evaporative cooling on mean temperature at the zone. Additionally, the cooling effect of evapotranspiration may be cancelled out by the dominating effect of albedo changes as studies have shown (Jeong et al, 2011;Pearson et al, 2013;Shen et al, 2015), especially with the recent greening, which has a warming effect through reduced albedo (Forzieri et al, 2017;Bi et al, 2020).…”
Section: Spatial Trend Of Temperature and Precipitationmentioning
confidence: 99%